A bio-inspired cilia array as the dielectric layer for flexible capacitive pressure sensors with high sensitivity and a broad detection range. Issue 48 (25th November 2019) - Zhou, Qian; Ji, Bing; Wei, Yuzhang; Hu, Bin; Gao, Yibo; Xu, Qingsong; Zhou, Jun; Zhou, Bingpu
Abstract : A cilia array via a magnetic field was proposed as the dielectric layer for flexible capacitive sensors with high sensitivity and a broad detection range. Abstract : Recently, electronic skins that simulate the human sophisticated somatosensory system by transforming physiological signals into electrical signals have attracted considerable interest in various fields such as intelligence robots, human–machine interfaces, various wearable devices, etc. Herein, inspired by the human hairy skin, we reported a flexible capacitive pressure sensor with high sensitivity and a broad detection range using a hair-like micro cilia array (MCA) as the dielectric layer through a facile and cost-effective methodology. For the first time, we demonstrated that the MCA can be conveniently obtained with tunable morphologies taking advantage of the magnetic field simply from a portable magnet to serve as the dielectric layer for flexible capacitive pressure sensors. The shape controllability of the MCA structure was systematically investigated using various preparation parameters, e.g. the magnetic field, mass ratio of the composite, etc. With the optimized structure, the proposed sensor exhibits a high sensitivity of 0.28 kPa −1 (0–10 kPa), a broad detection range of up to 200 kPa (sensitivity of 0.02 kPa −1 within 50–200 kPa), a detection limit of 2 Pa and excellent structural robustness and stabilities. Practical applications such as pulse-sensing, voice recognition, gas-flow monitoring, high pressure monitoring (bending, walking, jumping, etc. ), spatial distributions, etc. were successfully demonstrated. Thanks to the facile and cost-effective fabrication approach as well as the outstanding sensing capability, the proposed pressure sensor can be of profound significance for future applications including wearable electronic devices, artificial intelligence, interactive robotics, and other actual fields.